Pemberdayaan Pustakawan dalam Meningkatkan Kecakapan Administrasi Melalui Workshop Administrasi di SDN 005 Teluk Pandan - Saera, Karmila; Khoirunnisa, Mufliha; Mubarok, Ramdanil; Prima, Anggra; Syafi’i, Muhammad Imam (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2024)
This service was carried out to improve the administrative skills of librarians at SDN 005 Teluk Pandan. Through this workshop, library administration can improve the efficiency, productivity, and quality of services provided by librarians. The method used in this service is the Participatory Action Research (PAR) method. Workshop participants consisted of librarians and school administration staff. The results of the service show that the administration workshop is effective in increasing librarians' understanding of the principles of library administration, collection management, and library administration. In addition, this workshop also facilitates interaction between participants, strengthens practical skills, and increases confidence in managing administrative tasks. Another result was the creation of a new SDN 005 Teluk Pandan Library Member Card and a book code, which was successfully created and affixed to the SDN 005 Teluk Pandan library book collection. This service provides an important contribution to understanding the role of administrative workshops in improving the skills of librarians in the context of basic education. The practical implication of this research is the importance of investing in training and empowering librarians to improve the quality of library administration services in elementary schools